Peran Festival Budaya Dalam Pengembangan Nilai Religius Dan Nilai Sosial Di Desa Gosari Kecamatan Ujungpangkah Kabupaten Gresik - Aldi Wahyu Saputra; Akhmad Qomaru Zaman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Cultural festivals are a series of positive activity processes conducted in certain areas to maintain and preserve local and national culture. They are held to include the participation of the community, related parties, and the government together. This research was a type of qualitative research conducted in Gosari Village, Ujungpangkah District, Gresik Regency. Data sources were obtained from the Village Head, Chief Executive, Head of WAGOS Board (Gosari Natural Tourism), religious, and community leaders, and supported by documents and archives. Data collection was conducted through interviews, observation, and documentation techniques. The research findings showed that the Gosari cultural festival is held once a year with a series of activities which include: Resik Sendang Icleaning the bathing place), Kirab Warga (mutually cleaning the environment), Ngadusi Rojo Koyo (bathing the cows), Traditional Snacks Market, review of the book: “History and Mythology of Gosari”, Performance of Traditional Dance and Ludruk Art. The values developed in the implementation process are social, religious, and traditional values. Cultural festivals play a role in developing religious and social values, namely through the optimization in the field of education which is collaborative with nature, and the habituation of community traditions which are held regularly and continuously.